2016
DOI: 10.5578/tt.9142
|View full text |Cite
|
Sign up to set email alerts
|

Metered dose inhaler-spacer use education effects on achieve asthma control in children

Abstract: SUMMARYMetered dose inhaler-spacer use education effects on achieve asthma control in children

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 29 publications
1
8
0
1
Order By: Relevance
“…So, proper education for asthmatic children can acquire the necessary knowledge, skills and confidence as well as engaging in proper behavior to control or reduce the effect of asthma, and collaborate with nurse in order to be active partners in the treatment. This finding agrees with Ranaut et al (2013) and Türkeli et al (2016)studies which proved that repetitive demonstrations regarding use of MDI of appropriate technique is an effective method for improving performance regarding the use of the inhaler with or without spacer and asthma control in children. Additionally Kalaldeh et al (2016) added that Nurse-driven inhaler education enhanced inhaler proficiency scores and adherence while before implementation participants showed insufficient knowledge of general inhaler use, with difficulty use and complications from using the inhalers.…”
Section: Discussionsupporting
confidence: 81%
“…So, proper education for asthmatic children can acquire the necessary knowledge, skills and confidence as well as engaging in proper behavior to control or reduce the effect of asthma, and collaborate with nurse in order to be active partners in the treatment. This finding agrees with Ranaut et al (2013) and Türkeli et al (2016)studies which proved that repetitive demonstrations regarding use of MDI of appropriate technique is an effective method for improving performance regarding the use of the inhaler with or without spacer and asthma control in children. Additionally Kalaldeh et al (2016) added that Nurse-driven inhaler education enhanced inhaler proficiency scores and adherence while before implementation participants showed insufficient knowledge of general inhaler use, with difficulty use and complications from using the inhalers.…”
Section: Discussionsupporting
confidence: 81%
“…Four of the studies that had investigated symptom frequency found no differences, [26][27][28][29] and 25 studies reported reduction of symptoms and/or awareness of symptom triggers. Ten studies from interventions tailored to children and adolescents with asthma reported improved asthma control 51,[55][56][57][58][59][60] and decreased number of asthma exacerbations. 38,55,56,61,62 One study found no changes in asthma control.…”
Section: Psychosocial Outcomesmentioning
confidence: 99%
“…The patients were asked to use metered-dose inhaler and rated with a score ranging between 0 and 6 . For the preparation of scoring questions; Türkeli A et al questions have been modified 6 . Errors and deficiencies of use were re-explained.…”
Section: Methodsmentioning
confidence: 99%